CRIMINOLOGICAL UNDERSTANDING OF RELIGIOUS EXTREMISM - Burmistrov, Igor Alexeevich; Mironova, Elena Anatolevna; Ivanovich , Sergey; Nikodimov, Igor Yurievich (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the criminological study of religious extremism. Any manifestation of extremism is more or less inherent in the political content in the face of the confrontation of various social systems. This is unavoidable even when extremist leaders and others involved in illegal activities are unaware of the political implications of their actions. Therefore, the authors conduct a brief criminological analysis of criminal religious extremism, identify some facts of its formation and attempts to justify it theologically, reveal the anti-social content and techniques of criminogenic activity, and make some judgments about the prevention of this socially negative phenomenon. Religious extremism in Russia needs to be given constant and very close attention. What is this phenomenon? What are the factors that generate it? Who directs religious and extremist activities: foreign "conductors" or their leaders? By answering these questions, it is possible to understand this phenomenon and develop prevention measures.